The influence of leadership style, organizational design, and communication on employee performance at the head office and branches at PT XYZ company - Henny Agnecia Uliarta Simbolon; Okder Pendrian (Institute of Computer Science (IOCS), 2023)
This study aims to determine the effect of leadership style, organizational design, and communication on employee performance at the head office and branches at PT XYZ company. This research was conducted to examine how the style of leadership between the head office and branches supports employee performance, how influential the organizational design is in the PT XYZ company to collaborate between central and branch employees through what kind of communication so that each employee at the center and branches can be responsible for doing and completing work. The population in this study amounted to 100 employees of the center and branches. The data used is the result of questionnaire distribution data. This study uses multiple regression analysis models. Based on the results of the hypothesis in this study, it shows that Leadership Style, Organizational Design, and Communication together have a positive and significant influence on Employee Performance at the head office and branches at PT XYZ company.